THE IMPACT OF PARENTING PATTERNS ON SOCIAL-EMOTIONAL CHILDREN DEVELOPMENT - Alissa Ernawati Adisiswanto; Noor Faridha (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Parents in a family have a big responsibility in raising their children. An important part of building character is being a good parent. You can shape a person's character by teaching him values. Children learn religious and social values ​​from the way their parents treat them. This goal can be achieved if parents use the right parenting style. This is because the parenting style experienced by children will affect their social and mental growth. Therefore, parents need to learn more about how children develop social and emotional skills so that these skills develop well and can be accepted by society. The purpose of this study is to describe how parents help their children learn social and mental skills. The type of research carried out was qualitative research. This study was attended by all parents who had children aged between 9 and 12 years. The research was conducted in Bangsalsari, Jember, East Java, Indonesia. Observations and conversations are used to collect data. The triangulation method and Milles and Huberman theory can be used to check the validity of the data. Research findings show that parents have formed a democratic pattern towards their children by listening to and supporting their ideas. Authoritarian and loose parenting styles are not widely applied by parents who have their own children.